Perforansinsuffizienz - Korsake, K. (Phlebologie, 2018)
Perforansvenen verbinden die epifaszialen Beinvenen mit den subfaszial gelegenen tiefen Venen und dienen zur Drainage des venösen Blutflusses. In der Diagnostik und Therapie einer Varikosis haben die Perforansvenen eine große Bedeutung beim Aufsuchen des proximalen und distalen Insuffizienzpunkt. Die Untersuchung der Perforansvenen ist eine Herausforderung in der Duplexsonographie. Die pathophysiologisch bedeutsamen insuffizienten Perforansvenen sollten operativ oder minimal invasiv ausgeschaltet werden.Perforating veins connect the superficial and deep venous system. In the diagnosis and treatment of varicosis, perforating veins are of high importance in search for the most proximal and most distal point of insufficiency. The examination of the perforating veins is a challenge in duplex sonography. The pathophysiological relevant significant incompetent perforating veins should be treated with surgical or minimal invasive methods.
Keywords: Perforansvenen; Varikosis; Duplex; Veneninsuffizienz